Phototropic behavioral responses of zooplankton in Lake Baikal in situ and during the anthropogenic impact modeling - Dyomin, Victor V.; Morgalev, Yuri N.; Polovtsev, Igor G.; Morgalev, Sergei Yu; Morgaleva, Tamara G.; Davydova, Alexandra Yu; Kondratova, Oksana (Water)
Earlier, we showed that the registration of the behavioral responses of autochthonous mesozooplankton communities in situ is a more dynamic methodological approach in the biological assessment of the environmental well-being of aquatic ecosystems, as well as an alternative method to generally accepted tests on mortality and immobilization. The change in behavioral responses, including phototropic responses, may occur at lower concentrations of pollutants, leading to the inhibition of the risk-avoidance response of predatory fish attack and, ultimately, to the change in zooplankton abundance and biodiversity. The biological significance of such changes is quite high since zooplankters form the basis of food chains. This work studies the possibility of biomonitoring the quality of fresh water in Lake Baikal according to the state of the autochthonous mesozooplankton community in summer and winter using a digital holographic camera developed and tested by us in laboratory conditions. This method makes it possible to determine the concentration of plankters in the controlled volume of the DHC and perform photostimulation with different levels of illuminance. The depth profilometry of the phototropic response was compared with the profilometry of plankton concentration, intraspecific diversity of crustaceans according to the Pielou index, and the results of catching using the Juday net in the natural environment of the lake and during the modeling of the anthropogenic impact (introduction of table salt solution into the local area close to the registration probe). The circadian rhythm parameters were determined by the spectral analysis of the long-term registration of the phototropic response dynamics. It was noted that the inhibition of the phototropic response was the most adequate marker of the exogenous impact and the appearance of an alternating factor among the studied indicators of the state of the plankton community, namely, intraspecific diversity, synchronism of circadian rhythms, and response to paired photostimulation. The revealed patterns of behavioral responses of autochthonous zooplankton in natural and artificially modified conditions will allow for the implementation of long-term continuous control over the environmental well-being of water areas, including the collection ponds of treatment facilities, cooling ponds of nuclear power plants, and other water areas in contact with potentially hazardous facilities. The comparison of the identified patterns with the behavioral responses of euryhaline mesozooplankton will expand this method to assess the well-being of salt-water and marine reservoirs under the anthropogenic impact and will make it possible to create a continuous monitoring system.